T cell and B cell reactivities of leprosy patients and their contacts against antigens or epitopes Mycobacterium leprae - Hardyanto Soebono Hardyanto Soebono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
This study was aimed at evaluating the T cell and B cell reactivity against Mycobacterium leprae antigens or epitopes among leprosy patients and their household contacts in the Indonesian population. Through this study, M. leprae epitopes (either protective or suppresive) will be identified and hopefully proved useful for the development of an effective leprosy vaccine in the future.Fifty-nine leprosy patients consisting of 34 tuberculoid type (TT/BT) and 24 lepromatous type (LUBL) at Dr. Sardjito General Hospital Yogyakarta and 50 household contacts were recruited for this study. After the informed consent was given, 20 ml venous blood was drawn from each subject for assays of the T cell and B cell reactivities. The T cell reactivity was tested by lymphocyte transformation (LTT) and the B cell reactivity was tested serologically by EUSA. M. leprae antigen, PGL-1 and some recombinant proteins (65 kD, 30 kD, 45 kD and 43 kD) were used as antigens in both assays. In addition, Phytohemagglutinin (PHA) and lnterleukin-2 (IL-2) were used as mitogens in the LTT. Statistical analysis was done by using One way ANOVA and Chi-square tests.The results showed that cellular immune deficiency in LUBL patients was found to be specific to the M. leprae antigen, but not to mitogens and other antigens. The T-lymphocyte of the patients (either TT/BT or LUBL) and healthy contacts demonstrated very low reactivities againts all recombinant antigens. On the other hand, the sera of LL/BL leprosy patients reacted significantly against all antigens, most strikingly against PGL-I and 43 recombinant protein of M. leprae. Whereas, the sera of TT/BT patients and healthy contacts showed no or least reactivity against those antigens. These data indicate that although in a small proportion M. leprae recombinant proteins of 65 kD, 30 kD, 45 kD and 43 kD are recognized by T-cell of leprosy patients and healthy contacts. These antigens contain more B-cell epitopes rather than T-cell epitopes. So, these antigens should be eliminated. as soon as a possible candidate in the development of any leprosy vaccine.Key words: leprosy - T-cell and B-cell - Mycobacterium leprae antigen - ELISA - tuberculoid and lepromatouse types